Household Duck Farming and Rural Livelihoods in Serey Sophorn Municipality, Banteay Meanchey Province, Cambodia - Pisith Rath; Kongkea Chhay; Maly So (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the Study: This study examines the economic performance and livelihood significance of household duck farming in Serei Sophon Municipality, Banteay Meanchey Province, Cambodia, with particular attention to its contribution to rural livelihoods and local economic development. Methodology: The research employed a case-study approach based on an egg-producing household farm in Phneat sub-district that maintained 3,500 laying ducks over one production cycle. Primary data were collected from the farm’s production and financial records, including costs, revenues, and management practices. Main Findings: The results show that household duck farming is a profitable enterprise, generating 4.50 riels in revenue for every 1 riel invested, with an economic efficiency ratio of 4.50 and a net profit of 328,992,600 riels per cycle. Break-even analysis indicated that only 14,810 eggs were required to cover total costs, far below the farm’s annual output of 960,000 eggs. SWOT analysis further identified major strengths, including capital self-reliance and low labour requirements, as well as constraints such as limited technical knowledge, disease risks, and dependence on external duckling suppliers. Novelty/Originality of This Study: This study contributes original insight by linking farm-level economic analysis with broader rural livelihood and local development perspectives in the Cambodian context. It highlights the potential of household duck farming as both a profitable agricultural enterprise and a livelihood strategy, while also identifying practical constraints that must be addressed to ensure long-term sustainability.